ANALISIS MENGENAI PERTANGGUNGJAWABAN PENGEMBANG RUMAH SUSUN TERKAIT KETIADAAN SERTIFIKAT LAIK FUNGSI MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2011 TENTANG RUMAH SUSUN JUNTO UNDANG-UNDANG NOMOR 28 TAHUN 2002 TENTANG BANGUNAN GEDUNG (STUDI KASUS APARTEMEN PARAMA CILANDAK JAKARTA SELATAN) - Octavianna Evangelista; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2018)
Building Worthiness Certificate is the certificate given by the Regional Government to those buildings that are completely built and already fulfilled all the requirements such as Technical and Administrative Requirements. Building Worthiness Certificate is the evidence to prove that the building is worth on the function. Building Worthiness Certificate is the government's effort to put the safety aspects on the first priority.Based on the Law of the Republic of Indonesia Number 28 of 2002 concerning Buildings, it says the Building Worthiness Certificate must be owned by the developers, with no exceptions to an apartment as it is stated in the Law of The Republic of Indonesia Number 20 of 2011 concerning apartments.Building Worthiness Certificate will be published if all the parameters of the worthiness has been satisfied such as safety, health, comfort and convenience aspects.In fact, the act of the developer has violated the laws. As a result of that, the building of the apartment was on fire. The purpose of this study is to determine the responsibility of the developer as it is the consequence of violating the laws.